Gallbladder perforation in a patient undergoing PCNL: Case report and literature review - Alessandro Vengjer; André Segura da Motta; Matheus Campos Alves Corrêa; Julia Corazza Nitta Yoshisaki; Marcelo Ribeiro de Azevedo; Olavo Napoleão de Araújo Neto (Urology Case Reports)
Percutaneous nephrolithotripsy (PCNL) is an effective therapeutic approach in cases of lithiasis, which is prone to complications. In this report we present a case of a 52-year-old female patient with recurrent episodes of lithiasis and, after PCNL, evolution with pain and abdominal distension on the 2nd post-operative day due to a perforation of the gallbladder. An exploratory laparotomy was performed, leading to clinical improvement, and the patient was discharged from the hospital on the 7th day after resolving the choleperitoneum. This report addresses a rare, life-threatening complication of PCNL with limited literature available on the subject.